The Prevalence of Diarrhea and Its Association With Drug Use in Elderly Outpatients: A Multicenter Study - Alberto Pilotto; Marilisa Franceschi; Dino Franco Vitale; Augusto Zaninelli; Francesco Di Mario; Davide Seripa; F. Rengo (2008)
OBJECTIVES To evaluate the prevalence of diarrhea and its association with drug use in elderly outpatients. METHODS The study was carried out by 133 general practitioners (GPs) who referred to 24 geriatric units in Italy. The demographic data, disability, gastrointestinal symptoms, and current medications were evaluated using a structured interview, including the evaluation of the activities of daily living (ADL), the instrumental activities of daily living (IADL), and the gastrointestinal symptoms rating scale (GSRS). RESULTS The study included 5,387 elderly subjects who regularly completed the structured interview. In total, 488 patients (9.1% of the whole population, 210 men and 278 women, mean age 75.6 ± 6.2 yr, range 65–100 yr) reported diarrhea, that is, items 11 and 12 of the GSRS, during the 7-day period before the interview. The prevalence of diarrhea significantly increased with older age (P= 0.025), the severity of ADL (P < 0.0001) and IADL disability (P < 0.0001), and the number of drugs taken (P= 0.0002). A multivariate analysis demonstrated that the presence of diarrhea was significantly associated with the use of antibiotics (odds ratio [OR] 4.58, 95% confidence interval [CI] 1.95–10.73), proton pump inhibitors (OR 2.97, 95% CI 2.03–4.35), allopurinol (OR 2.19, 95% CI 1.26–3.81), psycholeptics (OR 1.82, 95% CI 1.26–2.61), selective serotonin reuptake inhibitors (OR 1.71, 95% CI 1.01–2.89), and angiotensin II receptor blockers (OR 1.46, 95% CI 1.08–1.99), also accounting for sex, age, and the use of antidiarrheal agents and drugs for functional gastrointestinal disorders. CONCLUSION Diarrhea is a common problem in elderly outpatients. Its prevalence increases with old age, the severity of disability, and the number of drugs. Monitoring the presence of diarrhea and its complications in elderly patients who need treatments with drugs significantly associated with diarrhea may be clinically useful.